Trichobothrial morphology of Theraphosidae and Barychelidae spiders (Araneae, Mygalomorphae) - Guadanucci, José Paulo Leite (Zootaxa, 2012)
Clavate trichobothria are present on tarsi of all Theraphosidae and some Barychelidae spiders. They are also here reportedon the tibiae of some theraphosids. A comparative analysis of their occurrence is presented. Representatives of allsubfamilies of Barychelidae and Theraphosidae were studied. The following morphological patterns were recognized:filiform, thickened, and clavate. The surface of these trichobothria can be plumose or non-plumose. Five patterns in thedisposition of clavate trichobothria on tarsi, were recognized: 1—two parallel rows; 2—two diverging rows; 3—onenarrow, long median row; 4—one wide central row, intermixed with short covering setae; 5—a short row, restricted to thedistal half of the tarsus. The disposition of trichobothria on tibiae did not differ among the taxa examined, except for thoseon lateral surfaces, where they can form a row or be grouped. Some patterns of morphology and distribution can be usedas diagnoses of subfamilies and genera (e.g., Aviculariinae, Ischnocolus, Heterothele). The significance of such patterns in systematics is discussed and the usage in phylogeny is proposed.